AMPK Activator O304 Protects Against Kidney Aging Through Promoting Energy Metabolism and Autophagy - Zhu, Mingsheng; Shen, Weiwei; Li, Jiemei; Jia, Nan; Xiong, Yabing; Miao, Jinhua; Xie, Chao; Chen, Qiyan; Shen, Kunyu; Meng, Ping; Li, Xiaolong; Wu, Qinyu; et al. (Frontiers in Pharmacology, 2022)
Aging is an important risk factor for kidney injury. Energy homeostasis plays a key role in retarding aging, and mitochondria are responsible for energy production. In the kidney, renal tubular cells possess high abundance of mitochondria to meet the high energy consumption. AMPK is an evolutionarily conserved serine/threonine kinase which plays a central role in maintaining energy homeostasis and mitochondrial homeostasis. Besides that, AMPK also commands autophagy, a clearing and recycling process to maintain cellular homeostasis. However, the effect of AMPK activators on kidney aging has not been fully elucidated. To this end, we testified the effects of O304, a novel direct AMPK activator, in naturally aging mice model and D-Galactose (D-Gal)-treated renal tubular cell culture. We identified that O304 beneficially protects against cellular senescence and aged-related fibrosis in kidneys. Also, O304 restored energy metabolism, promoted autophagy and preserved mitochondrial homeostasis. Transcriptomic sequencing also proved that O304 induced fatty acid metabolism, mitochondrial biogenesis and ATP process, and downregulated cell aging, DNA damage response and collagen organization. All these results suggest that O304 has a strong potential to retard aged kidney injury through regulating AMPK-induced multiple pathways. Our results provide an important therapeutic approach to delay kidney aging.